Derandomization Security of Homomorphic Encryption - A. . Trepacheva (Труды Института системного программирования РАН, 2018)
The paper considers the problems of developing and analysis of cloud database systems. We determine the requrments for encryption to be usable in practical applications. A new notion - a non-derandomizable encryption - allows to do this and we explain the practical value of this notion as well as links between it and classical notions of cryptosystem’s security, practical security of whole cloud computing system. We show the examples of simple algebraically homomorphic cryptosystems - both derandomizable and not non-derandomizable. The paper finally concludes about usability of considered cryptosystems for practical cloud systems.